Are Mycoplasma hominis, Ureaplasma urealyticum and Ureaplasma parvum Associated With Specific Genital Symptoms and Clinical Signs in Nonpregnant Women?. (27th January 2021) - Plummer, Erica L; Vodstrcil, Lenka A; Bodiyabadu, Kaveesha; Murray, Gerald L; Doyle, Michelle; Latimer, Rosie L; Fairley, Christopher K; Payne, Matthew; Chow, Eric P F; Garland, Suzanne M; Bradshaw, Catriona S
Abstract: Background: There is limited evidence supporting an association between Mycoplasma hominis, Ureaplasma urealyticum, and Ureaplasma parvum with symptoms or disease in nonpregnant women. However, testing and reporting of these organisms frequently occurs, in part due to their inclusion in multiplex-PCR assays for sexually transmitted infection (STI) detection. We investigated if M. hominis, U. urealyticum, and U. parvum were associated with symptoms and/or signs in nonpregnant women attending a sexual health service. Methods: Eligible women attending the Melbourne Sexual Health Centre completed a questionnaire regarding sexual practices and symptoms. Symptomatic women underwent examination. Women were assessed for bacterial vaginosis (BV) and vulvovaginal candidiasis (VVC), and tested for M. hominis, U. urealyticum, and U. parvum, and 4 nonviral STIs using a commercial multiplex-PCR. Results: 1272 women were analyzed. After adjusting for STIs and VVC, M. hominis was associated with abnormal vaginal discharge (aOR = 2.70, 95%CI:1.92–3.79), vaginal malodor (aOR = 4.27, 95%CI:3.08–5.91), vaginal pH > 4.5 (aOR = 4.27, 95%CI:3.22–5.66), and presence of clue cells (aOR = 8.08, 95%CI:5.68–11.48). Ureaplasma spp. were not associated with symptoms/signs. Bacterial vaginosis was strongly associated with M. hominis (aOR = 8.01, 95%CI:5.99–10.71), but was not associated with either Ureaplasma spp. In stratified analyses, M. hominis was associated with self-reported vaginal malodor and clinician-recorded vaginal discharge in women with BV, but not with symptoms/signs in women without BV. Conclusions: Only M. hominis was associated with symptoms/signs, and these were manifestations of BV. Importantly, M. hominis was not associated with symptoms/signs in women without BV. These findings do not support routine testing for M. hominis, U. urealyticum, and U. parvum in nonpregnant women. Abstract : Ureaplasma spp. were not associated with clinical signs or symptoms in nonpregnant women. Mycoplasma hominis was associated with vaginal malodor and abnormal vaginal discharge in women with bacterial vaginosis (BV), but was not associated with symptoms/signs in women without BV.